Shari’ah-compliant Financing Mechanisms for Belt and Road Initiative: Mitigating Debt Trap Risks - Shabani, Ramadhani Mashaka (AL-ARBAH: Journal of Islamic Finance and Banking, 2024)
Purpose - The purpose of this study was to examine how Shari'ah-compliant finance can be a solution in financing BRI projects and mitigating debt risk.Method - The study uses a systematic literature review.  Result - The finding shows that Shari'ah-compliant finance can provide a solution to the debt trap associated with the conventional model proposed by the Chinese government. By using BOT, the structure can facilitate financing, especially in developing countries with no technical skills as well as experience in operating massive projects. This structure offers financing of the project as well as helps in skills transfer to the local during the operating stage. Another structure is Istisna’s lease Finance, this structure focuses on financing the specific project identified by the country. This structure offers the country the ability to develop the project, lease the project, and pay back a specific amount in instalments. Despite the conventional finance where the payment contains interest, in this contract the payment is specified and cannot be changed due to interest.Implication - The study uses shari'ah-compliant financing mechanisms for belt and road initiative to mitigating debt trap risks.Originality - BRI projects are crucial for the development of the countries. The Chinese government established BRI to try to connect Asia, the Middle East, Europe, and Africa through massive infrastructure such as roads, railways, ports, and airports. However, there is a challenge in financing these projects.  Sharia-compliant Financing Mechanisms to mitigating debt trap risks.